The universal structure of categories : towards a formal typology - Wiltschko, Martina (Cambridge, United Kingdom : Cambridge University Press, 2014)
"Using data from a variety of languages such as Blackfoot, Halkomelem, and Upper Austrian German, this book explores a range of grammatical categories and constructions, including tense, aspect, subjunctive, case and demonstratives. It presents a new theory of grammatical categories - the Universal Spine Hypothesis - and reinforces generative notions of Universal Grammar while accommodating insights from linguistic typology. In essence, this new theory shows that language-specific categories are built from a small set of universal categories and language-specific units of language. Throughout the book the Universal Spine Hypothesis is compared to two alternative theories - the Universal Base Hypothesis and the No Base Hypothesis. This valuable addition to the field will be welcomed by graduate students and researchers in linguistics"--
Machine generated contents note: 1. The universal structure of categories; 2. A history of ideas behind the spine; 3. The universal spine as a heuristic for the identification of grammatical categories; 4. Anchoring categories in independent clauses; 5. Anchoring categories in dependent clauses; 6. Nominal anchoring categories; 7. Categories that introduce a point of view; 8. Towards a formal typology.
Includes bibliographical references (pages 327-351) and index.
Keywords: CATEGORIAL GRAMMAR; STRUCTURAL LINGUISTICS; LANGUAGE, UNIVERSAL